Location of the study area. - Çağrı Mercan (22559879) (2025)
Country boundaries were obtained from Natural Earth (public domain). Administrative boundaries were derived from the General Directorate of Mapping, Türkiye (open-access vector data, no copyright restrictions). Beekeeper location data were collected by the authors during field surveys using GPS devices. All maps were created by the authors using publicly available datasets processed in ArcGIS without any proprietary basemap. No copyrighted material was used.